2014
DOI: 10.1145/2584652
|View full text |Cite
|
Sign up to set email alerts
|

Near optimal rate selection for wireless control systems

Abstract: Abstract-With the advent of industrial standards such as WirelessHART, process industries are now gravitating towards wireless control systems. Due to limited bandwidth in a wireless network shared by multiple control loops, it is critical to optimize the overall control performance. In this paper, we address the scheduling-control co-design problem of determining the optimal sampling rates of feedback control loops sharing a WirelessHART network. The objective is to minimize the overall control cost while ens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
2

Relationship

4
5

Authors

Journals

citations
Cited by 64 publications
(34 citation statements)
references
References 28 publications
0
34
0
Order By: Relevance
“…Case studies on wireless structural monitoring and control systems were reported in [20,21,27,28]. Realtime transmission scheduling and co-designs for WSANs has been investigated in [11,24,25,31]. Reliable routing algorithms for WSANs have been presented [15].…”
Section: Related Workmentioning
confidence: 99%
“…Case studies on wireless structural monitoring and control systems were reported in [20,21,27,28]. Realtime transmission scheduling and co-designs for WSANs has been investigated in [11,24,25,31]. Reliable routing algorithms for WSANs have been presented [15].…”
Section: Related Workmentioning
confidence: 99%
“…Han et al [7] presented a graph routing algorithm. Saifullah et al presented a series of theoretical results on real-time transmission scheduling [13], rate selection for wireless control [12], and delay analysis [14,16]. All these works are based on theoretical analysis and simulation studies.…”
Section: Related Workmentioning
confidence: 99%
“…Actually, the desired sampling rate may be obtained based on network performances and control performances, and [31] has provided a solution. In this paper, our efforts are focused on providing a control scheme that guarantees the sampling period to track the desired value.…”
Section: Adaptive Tracking Controller Designmentioning
confidence: 99%